Chapter 7. Challenges and opportunities of pearl millet hybrid development and seed production in West Africa - Gangashetty, Prakash I.; Inoussa, Drabo; Kanfany, Ghislain; Rakshith, P.; Mohammed Riyazaddin; Diack, Omar; Serba, Desalegn D.; Perumal, Ramasamy (2024)
Enhancing agricultural productivity in response to the growing population and food demand in West Africa is imperative. Pearl millet [ Pennisetum glaucum (L.) R. Br.], which is well suited to the region's challenging conditions, holds significant potential for strengthening food security. However, current yields are low, and the adoption of improved hybrid varieties lags. Organizations like International Crop Research Institute for the Semi-Arid Tropics and national agricultural research institutes are working to establish hybrid breeding programs, emphasizing harnessing heterosis for higher yields and stress resilience, but challenges include finding suitable cytoplasmic male sterility sources and developing restorer lines. Initiatives by the Alliance for Green Revolution in Africa and Harvest Plus support hybrid development, as evidenced by Burkina Faso's release of Nufagnon, a high-yield, downy mildew–resistant hybrid adapted to local conditions. Key to success is addressing agronomic and socio-economic challenges through collaboration with farmers, optimizing planting density, and ensuring proper fertilizer use. Public and private sectors play vital roles, requiring training for local seed companies, incentivizing hybrid seed production, and implementing policies to prevent malpractice. Ongoing genetic research, including identifying heterotic groups and utilizing advanced molecular techniques, is crucial for shaping hybrid development. The outlook is promising, with collaborative efforts expected to yield improved hybrid varieties. The adoption of "speed breeding" and precision breeding techniques holds potential for quicker adaptation to changing agricultural landscapes. In conclusion, success hinges on continued collaboration, favorable policies, and concerted efforts to address challenges, ultimately enhancing food security and fostering economic growth in the region.